The Socialist People's Libyan Arab Jamahiriya : Selected Issue; Medium-Term Economic Reform Strategy, and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper aims to present a medium-term reform strategy that could be pursued by Libya to accelerate its transition to a market economy. The paper reviews the main characteristics of the Libyan economy, and medium-term prospects under current policies. It examines the priority reforms that Libya needs to implement to accelerate its transition to a market economy, while maintaining macroeconomic stability. The paper also reviews a second set of reforms that aim to consolidate the reform process and advance the restructuring of the economy in favor of the non-oil sector.